2014
DOI: 10.1002/ps.3700
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fusarium oxysporum in fumigated soils by a newly developed real-time PCR assay to assess the efficacy of fumigants for Fusarium wilt disease in strawberry plants

Abstract: This study confirms that the newly developed real-time PCR quantitative assay for F. oxysporum was suitable for the control efficacy evaluation of soil fumigants and that the novel fumigant combination of CP and DMDS offers a promising effective alternative to MB for the control of F. oxysporum in strawberry greenhouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…The other tested fumigant metam sodium also induced a significant reduction in the population of F. oxysporum, which lasted for 60 days. Our data are in agreement with findings by Li et al (2014) who showed that DMDS, when used alone or in combination with chloropicrin, substantially reduced the population of F. oxysporum with reduction levels of 54-58 % (DMDS), 77-79 % ( D M D S : C h l o r o p i c r i n 2 : 1 ) a n d 8 7 -8 8 % (DMDS:Chloropicrin 1:2). In similar studies the application of DMDS alone or in combination with dazomet ), or chloropicrin (Basallote-Ureba et al 2010 significantly reduced the incidence of F. oxysporum in cucumber and carnation plants respectively.…”
Section: Impact Of Fumigants On F Oxysporumsupporting
confidence: 95%
See 1 more Smart Citation
“…The other tested fumigant metam sodium also induced a significant reduction in the population of F. oxysporum, which lasted for 60 days. Our data are in agreement with findings by Li et al (2014) who showed that DMDS, when used alone or in combination with chloropicrin, substantially reduced the population of F. oxysporum with reduction levels of 54-58 % (DMDS), 77-79 % ( D M D S : C h l o r o p i c r i n 2 : 1 ) a n d 8 7 -8 8 % (DMDS:Chloropicrin 1:2). In similar studies the application of DMDS alone or in combination with dazomet ), or chloropicrin (Basallote-Ureba et al 2010 significantly reduced the incidence of F. oxysporum in cucumber and carnation plants respectively.…”
Section: Impact Of Fumigants On F Oxysporumsupporting
confidence: 95%
“…With the exception of the recent study by Li et al (2014) all other studies that have investigated the impact of fumigants including DMDS on the population dynamics of soil borne fungal pathogens they have utilized cultivation-based methods (Singleton et al 1992). The latter are time-consuming and do not provide an accurate estimation of the fungal population due to the proven limited selectivity of the growth media used (Thorn et al 1996;Termorshuizen et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…lycopersici , but the expression of the disease was not prevented in lettuce ( Lactuca sativa L.). Similarly, Li et al . reported that DMDS + Pic was more effective than DMDS alone and successfully suppressed the incidence of Fusarium wilt in strawberry ( Fragaria × ananessa Duchesne).…”
Section: Resultsmentioning
confidence: 90%
“…DMDS primarily affects mitochondrial respiration through blocking the activity of the enzyme cytochrome oxidase . DMDS has proven to be an effective fumigant for control of Cyperus spp . and other soilborne pathogens such as Fusarium oxysporum and Meloidogyne nematodes .…”
Section: Introductionmentioning
confidence: 99%
“…The assay was also successfully applied for the qualitative and quantitative analysis of Fusarium species in contaminated maize samples . Li et al conducted a real‐time PCR assay based on the FOW1 gene encoding a mitochondrial carrier protein for detection and quantification of F. oxysporum , by which a strong positive correlation was found between the copy number (×10) of the F. oxysporum FOW1 gene in 5 g of soil and the colony forming unit (CFU) number . Furthermore, a DNA microarray for easy and fast detection of trichothecene‐ and moniliformin‐producing Fusarium species has been developed, which has the capture probes designed by the tef‐1α sequence.…”
Section: The Use Of Polymerase Chain Reaction For Detecting Fusarium mentioning
confidence: 99%